Compliance management a how-to guide for executives, lawyers, and other compliance professionals - Singh, Nitish 1972-; Bussen, Thomas J. (Praeger, 2015)
"This practical guide shows how to build an effective compliance and ethics program that will lower a business's risks and improve productivity"..